Research on Output Performance of Linear Motor Reciprocating Pump Based on Mechanical-Hydraulic-Load Coupling Model - Jinbo Xiang; Zhiqiang Wang; Lihong Li; Ziwei Qi; Xiaopeng Yue (Machines)
To study the output performance of the multi-unit linear motor reciprocating pump group, a mechanical-hydraulic-load coupling model was established based on the electromagnetic output model of the linear oscillating motor and the load model of the hydraulic pump system. The dynamic characteristics of the multi-unit linear motor reciprocating pump and the output performance under different input signal parameters were studied using the AMEsim-Simulink co-simulation method, and the validity of the simulation model was verified by the prototype output performance experiment. The analysis result indicates that the parameters of the input signal have a greater impact on the performance of the linear motor reciprocating pump. And the sine wave signal is more suitable as the control signal of the linear motor reciprocating pump, while the staggered parallel mode can greatly reduce the flow output pulsation rate of the even number pump group.